Correlations between the expression of molecules in the TGF-β signaling pathway and clinical factors in adamantinomatous craniopharyngiomas - Jin, Lu; Cai, Kefan; Wu, WenTao; Xiao, Youchao; Qiao, Ning; Liu, Fangzheng; Ru, Siming; Cao, Lei; Zhu, Haibo; Bai, Jiwei; Liu, Chunhui; Li, Chuzhong; et al. (Frontiers in Endocrinology, 2023)
Objective To investigate the clinical and pathological factors associated with preoperative hypothalamus invasion and postoperative outcomes of adamantinomatous craniopharyngiomas (ACPs) after the expanded endonasal approach (EEA) resection. Methods Ninety-three specimens of ACPs, consisting of 71 primary and 22 recurrent tumors, were investigated for the expression of TGF-β1, SMAD2, SMAD3, and β-catenin by immunohistochemistry staining. The clinical information of relevant patients, including the extent of resection, hypothalamus invasion, endocrinopathy, complications, and prognosis, was reviewed. The relationships between the expression of these immunopathological markers and clinical factors were analyzed. Results Endocrinological dysfunctions were more common in recurrent patients and primary patients with hypothalamus invasion in the comparisons. For recurrent patients, the rate of gross total resection (GTR) was significantly lower than for primary patients (63.6% vs. 90.1%, P = 0.007). According to radiological and intraoperative findings, invasive ACPs (IACPs) included 48 (67.6%) cases in primary tumors. The expression of TGF-β1 and β-catenin was significantly higher in recurrent tumors (P = 0.021 and P = 0.018, respectively) and IACPs (P = 0.008 and P = 0.004, respectively). The expression level of TGF-β1 was associated with hypothalamus involvement (Puget grade, P = 0.05; Vile grade, P = 0.002), postoperative endocrinopathy (P = 0.01), and pituitary stalk preservation (P = 0.008) in primary patients. In addition, the extent of resection, treatment history, hypothalamic invasion, and level of TGF-β1 expression had significant influences on tumor recurrence/progression after surgery separately. Conclusion Our study demonstrated the potential role of TGF-β1 in the regulation of hypothalamus invasion in ACPs and the prediction of prognosis after EEA surgery. The TGF-β signaling pathway may represent a crucial mechanism in the aggressive behavior and progression of ACPs.